Performans Klinis dan Pengobatan Pedet Sapi bali (Bos sondaicus) yang terinfeksi Toxocara vitulorum - Ribeiro, Ezequiel N.D; Simarmata, Yohanes T R M R; Tophianong, Tarsisius C (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2024)
Toxocara vitulorum is a nematode worm that is highly pathogenic in almost all breeds of cattle and buffaloes worldwide. Bali cattle are one of the main hosts, especially the calves. Calves begin to become infected after ingesting larvae from the mother through colostrum then migrating and causing damage to the organs which it passes. Therefore, this study aimed to determine the clinical symptoms, clinical performance, diagnosis and treatment of bali calves that infected with Toxocara vitulorum. The literatures used for this study were obtained from searching and collection of various reference sources using Mendeley and Google Scholar applications. Based on the results of the study, infected calves showed abnormalities such as lethargy, depression, dark brown and fishy-smelling diarrhea, anorexia, abdominal pain or colic, coughing, constipation, dehydration, pale mucous membrane, BCS below 3, poor growth or stunted, weight loss, dull hair, butyric-smelling breath, abdominal distension, respiratory rate 40 rpm and heart rate 84 rpm. The diagnosis of Toxocara vitulorum is based on clinical signs, necropsy findings, fecal examination, and serological tests. However, serological testing is an alternative method that is more suitable for diagnosis because it can identify Toxocara vitulorum in prepatic infections and mild infections in calves. A very effective serological test is ELISA. Modern anthelmintic that is highly recommended for the treatment of Toxocara vitulorum in bali calves is fenbendazole from the benzimidazole group, while the herbal anthelmintic recomended are knicker nut (Caesalpina crista) and wormwood (Artemisia maritima).